Niekontekstualne rozumienie kultury gospodarczej - Zboroń, Halina (Człowiek i Społeczeństwo, 2018)
Halina Zboroń, Niekontekstualne rozumienie kultury gospodarczej [Non-contextual understanding an economic culture] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 187–201, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The article aims to critical analyze the way of understanding an economic culture, especially a contextual approach which characterizes economists’ beliefs concerning as well economy as individuals participating in a social practice of production, exchange and consumption of goods and services. Moreover the author aims to present an alternative, non-contextual approach of an economic culture considered as a direct regulation of economic activities.